Intra-industry trade and revealed comparative advantage : an inverted-U relationship - Faustino, Horácio C. (2010)
This paper investigates the relationship between all types of intra-industry trade (IIT) and comparative advantage. The paper finds strong evidence of an inverted-U relationship.The results also suggest that relative autarky costs is a common determinant for any type of IIT, which contradicts the prediction made by theory for separating the determinants of horizontal and vertical IIT.